Peran Guru Dalam Memotivasi Siswa Pada Kegiatan Persiapan Tes Kompetensi Akademik - Himmah, Nurul; Wagiyem, Wagiyem; Nurul Laili; Atik Nurhidayati; Mustaqimah, Mustaqimah; Uswatun Khoiriyah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to describe the steps of teachers' role in providing motivation and the strategies implemented to improve students' readiness for the Academic Competency Test (TKA) at Madrasah Tsanawiyah Negeri 1 Klaten. The research subjects were teachers at Madrasah Tsanawiyah Negeri 1 Klaten. The informants for this study were teachers. The study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that teachers play a crucial role in mapping students' learning readiness and motivational profiles by identifying initial academic abilities, self-confidence levels, and psychological barriers. In addition, teachers establish warm and empathetic communication to create a safe learning environment so that students are more motivated and do not experience excessive anxiety. The learning strategies provided include step-by-step practice questions, problem-solving discussions, and reasoning-based learning that is appropriate to the characteristics of TKA. These activities have been proven to increase students' interest and academic readiness in facing high-standard questions. Teachers also apply motivational strategies such as positive reinforcement, simple rewards, and verbal appreciation to build students' confidence. Contextual learning based on real situations also increases intrinsic motivation and student engagement. Regular reflection and feedback are provided to monitor progress, identify weaknesses, and strengthen learning enthusiasm throughout the TKA preparation process. Overall, the combination of teacher roles and strategies contributes significantly to improving students' mental and academic readiness to face TKA.